Hong Kong Poison Information Centre: Annual Report 2013. Issue 4 (July 2014) - Chan, YC; Tse, ML; Lau, FL
Objective: To report and analyse the poisoning data of Hong Kong Poison Information Centre (HKPIC) in 2013. Methods: In 2013, all poisoning cases received by HKPIC were retrieved from its database [Poison Information and Clinical Management System (PICMS)] for analysis. Results: A total of 3, 783 poisoned cases were analysed. There were 1, 595 male patients (42.2%), 2, 185 female patients (57.8%) and 3 sex unspecified patients (0.1%). Middle aged group (30-39 years) composed about one-fifth (20.8%) of the poisoning cases while about two-third (66.8%) of them were between 20 and 59 years old. Common causes for poisoning were suspected self-harm/suicidal attempt (43%), unintentional exposure (15.3%) and abusive substances use (14.5%). Five commonest types of poison exposed were paracetamol, benzodiazepine, zopiclone, household products and Chinese herbal medicine. Majority of the patients were managed with supportive measures, and 13.2% and 10.8% of them were treated by decontamination and antidotes respectively. Most cases had uneventful recovery; 0.9% of the poisoning resulted in death and 4.3% had major outcomes. Conclusions: This 8 th annual report provided updated epidemiological information on poisoning pattern in Hong Kong and highlighted important changes in comparing with our previous reports. (Hong Kong j. emerg.med. 2014;21:249-259)